Paralelisme Hikmat dengan Pendidikan Kristen dalam Amsal 3:1-4 - Jefrie Walean (Jurnal Salvation, 2021)
Abstract: Christian education is a two-sided coin to build a life that has knowledge, understanding, and application of Christian values. Points about knowledge, understanding, and application become a reference in Christian education. The message in the book of Proverbs gives an understanding of wise behavior, truth, justice, honesty. This study aims to narrate the concept of wisdom in human life so that it can function as a guide for life. This research uses literature study and processed qualitatively descriptively to get a theoretical understanding. This study concludes that education and wisdom are integral parts in formulating the theoretical basis for Christian religious teaching. The principles of life taught in the text of Proverbs 3:1-4 are useful for guiding so as to form human characters who are physically and mentally healthy. Thus, wisdom becomes the primary basis for shaping one's behavior in that wisdom and Christian religious teaching becomes the primary basis for shaping one's behavior cognitively, affectively, psychomotorically.   Abstrak: Pendidikan kristen merupakan dua sisi mata uang untuk membangun hidup yang memiliki pengetahuan, pemahaman, dan penerapan nilai-nilai kristiani. Point tentang pengetahuan, pemahaman, dan penerapan menjadi acuan dalam pendidikan Kristen.  Pesan dalam  kitab Amsal memberi  pengertian mengenai perilaku yang bijak, kebenaran, keadilan, kejujuran. Penelitian ini bertujuan menarasikan konsep hikmat dalam kehidupan manusia sehingga dapat berfungsi sebagai penuntun kehidupan. Penelitian ini menggunakan studi kepustakaan dan diolah secara kualitatif deskriptif untuk mendapatkan pemahamanan teoritis. Penelitian ini menyimpulkan bahwa pendidikan dan hikmat merupakan bagian integral dalam menyusun landasan teori pengajaran agama Kristen. Asas-asas kehidupan yang diajarkan dalam teks Amsal 3:1-4 bermanfaat untuk membimbing sehingga membentuk karakter manusia yang sehat jasmani dan sehat rohani. Dengan demikian bahwa hikmat menjadi landasan primer  untuk membentuk perilaku seseorang dalam bahwa hikmat dan pendidikan Kristen menjadi landasan primer  untuk membentuk perilaku seseorang secara kognitif, afektif, psikomotorik.